Promoting pediatric oncology nursing excellence in sub-Saharan Africa using project ECHO - Marilyn Hockenberry; Rhahim Bank; Aisha Nedege; Tadala Mulemba; Joan Nakabiri; Mpho Raletshegwana; Pearl Semetsa; Jennifer Higgins (Elsevier, 2021)
Purpose: The designation of the year 2020 as the International Year of the Nurse provides time for reflection on the importance of nursing in meeting the needs of the under-served throughout the world. The purpose of this project was to implement an education network for nursing caring for children with cancer across sub-Saharan Africa. Methods: The Extension for Community Health Outcomes (ECHO) model is used by Global HOPE Nursing to implement a real-time internet based learning platform that provides nurses in sub-Saharan Africa with access to nursing expertise in the care of children with cancer. Case-based learning strategies are used at monthly Project ECHO nursing seminars to provide access to nursing expertise in the care of children with cancer. Early career nurses specializing in pediatric oncology are mentored to serve as Global HOPE Nursing Project ECHO presenters. Results: During the first ten months, 321 participants from 12 countries attended an ECHO seminar with an average of 32 participants per seminar. Participants felt more confident in providing childhood cancer nursing care after the Project ECHO seminar and evaluations demonstrated a case-based approach to learning was extremely successful. by the number of participants that continue to attend. Conclusions: A key focus of the Global HOPE Nursing Project ECHO is to build a knowledge network to increase capacity of pediatric oncology nursing experts in sub-Saharan Africa. This Project ECHO also enables early career nurses to develop skills and knowledge regarding how to mentor others. Innovative projects using learning platforms can be effective in promoting nursing specialization and fostering future nursing leaders in sub-Saharan Africa.